2017
DOI: 10.15277/bjd.2017.117
|View full text |Cite
|
Sign up to set email alerts
|

A global survey of licensing restrictions for drivers with diabetes

Abstract: Background: Ensuring medical fitness to drive is an important safety measure for people with diabetes and is a prerequisite for a driving licence in many countries. Objectives: To ascertain the current regulatory restrictions on drivers with diabetes currently being applied internationally. Methods: An electronic survey (in English) was sent to contacts of member organisations of the International Diabetes Federation and to selected specialists in diabetes. Questions addressed the regulations in place for insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…A recent international survey that included 85 countries revealed a total lack of licensing restrictions in 59 (69.4%) while medical assessment of some type was required in 29 (34.5%) countries. That survey has also revealed that the absence of statutory restrictions is more common in countries with lower economic status and is associated with higher rates of road traffic fatalities [7].…”
Section: Introductionmentioning
confidence: 94%
“…A recent international survey that included 85 countries revealed a total lack of licensing restrictions in 59 (69.4%) while medical assessment of some type was required in 29 (34.5%) countries. That survey has also revealed that the absence of statutory restrictions is more common in countries with lower economic status and is associated with higher rates of road traffic fatalities [7].…”
Section: Introductionmentioning
confidence: 94%
“… 21 Globally, there is a wide variation between different countries and regions in the statutory requirements and policies used to regulate and assess drivers with diabetes. 22 …”
Section: Hypoglycemia Driving and Licensing Standardsmentioning
confidence: 99%
“…In a recent international study, no restrictions on drivers with insulin-treated diabetes existed in 59 out of 82 surveyed countries (69.4%). 22 Lack of restrictions on licenses in drivers on insulin was evident in less developed countries, indicated by geographic basis and by using an established national social/political/economic index (gross domestic product). 22 …”
Section: Insulin-treated Diabetes and Drivingmentioning
confidence: 99%
“…A recent global survey of 85 countries revealed wide variation in practice and, surprisingly, many national diabetes organisations declined to provide information about the legislation (which is mostly non-existent) on the position regarding regulations for driving licensing in their countries. 9 Of the countries in South-East Asia who responded to this survey, none currently impose any form of licensing restriction on drivers with diabetes, unlike most countries in Europe, North America and Australasia. It was particularly disconcerting to find that, in two-thirds of those countries, no restriction is placed on the driving of large goods vehicles (Group 2 classification in Europe) by people with insulin-treated diabetes, and a 'call to arms' from concerned diabetes specialists in some of the countries with either no or less stringent regulation has been ignored.…”
Section: Can We Identify Drivers With Diabetes At Risk Of Road Traffimentioning
confidence: 99%